Durch Digitalisierung zur Freiheit 4.0? - Souvignier, Georg; Heidenklang, Frank (Wissenschaftliche Buchgesellschaft (wbg), 2021)
Do digital technical systems open up more and qualitatively new forms of freedom or do they tend to restrict them? In addition: Do artificial intelligence systems gain a freedom that is analogous to that of humans? This volume examines the relationship between digitization and freedom from technical and humanities perspectives.